Financial and sovereign debt crises: some lessons learned and those forgotten - Reinhart, Carmen M.; Rogoff, Kenneth S. (Washington, DC, 2013)
"Even after one of the most severe multi-year crises on record in the advanced economies, the received wisdom in policy circles clings to the notion that high-income countries are completely different from their emerging market counterparts. The current phase of the official policy approach is predicated on the assumption that debt sustainability can be achieved through a mix of austerity, forbearance and growth. The claim is that advanced countries do not need to resort to the standard toolkit of emerging markets, including debt restructurings and conversions, higher inflation, capital controls and other forms of financial repression. As we document, this claim is at odds with the historical track record of most advanced economies, where debt restructuring or conversions, financial Repression, and a tolerance for higher inflation, or a combination of these were an integral part of the resolution of significant past debt overhangs."